Bioactive phytochemical compounds characterization, anti-oxidant and anti-microbial activity of the methanol and acetonitrile leaf extracts of Pithecellobium dulce - M. Kiranmayee; K. Riazunnisa (Phytomedicine Plus)
Background: Numerous natural substances with various pharmacological properties can be discovered in medicinal plants. Pithecellobium dulce (Roxb.) Benth is a traditional medicinal plant, belonging to the family Leguminosae. The various parts of the P. dulce plant are traditionally used to treat a wide range of health disorders in numerous countries. Purpose: The aim of this investigation is to demonstrate the phytochemical profiling of methanol and acetonitrile leaf extracts of P. dulce and evaluate their antioxidant activity and antibacterial potential against pathogenic bacteria. Materials and methods: The methanol and acetonitrile extracts of P. dulce leaf were extracted and characterized by using GCMS– and FTIR. Further evaluation was done for an understanding of the biomedical uses of P. dulce. The antibacterial activity of the extracts was monitored against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. The antioxidant activity of extracts was conducted by using DPPH and hydrogen peroxide scavenging activity, and total antioxidant activity was performed by phosphomolybdenum assay. Results: A total of twenty-three compounds were tentatively identified through GC–MS; five of these were associated with the methanolic extracts, while eighteen were with the acetonitrile extract. The tentatively identified compounds present in acetonitrile leaf extract were 2-nonynoic acid; pentane, 2,4-dimethyl-; lupeo; phytol; propiolic acid; bicyclo(2.2.1), and heptane-5-(ethyl-1-amine). Propanamide; N-methyl-2-amino-; ethane, 1‑chloro-1-fluoro; nitrous oxide; oxirane, (ethoxymethyl)- and 2,5-cyclooctadien-1-ol were the compounds found in methanol extract. FTIR analysis identified various functional groups in the leaf extracts, indicating the presence of alcohols, phenols, unsaturated and saturated hydrocarbons, amines, flavonoids, and halogenated compounds. Acetonitrile and methanolic P. dulce leaf extracts exhibited significant antioxidant and antibacterial properties. Methanolic and acetonitrile leaf extracts exhibited the highest zone of inhibition against E. coli (21 ± 1.1 mm) and B. subtilis (20.6 ± 0.5 mm). Conclusion: This study highlighted the presence of different phytochemicals that showed anti-bacterial and antioxidant activities. Therefore, P. dulce leaf extracts may play a significant role in inhibiting human infections.